The Prevalence of Polycystic Ovary Syndrome in Women with Idiopathic Intracranial Hypertension - Inbal Avisar; Dan D. Gaton; Hirsch Dania; Hadas Stiebel-Kalish (Scientifica)
Purpose. The purpose of this study is to re-evaluate whether the prevalence of polycystic ovary syndrome (PCOS) amongst women with idiopathic intracranial hypertension (IIH) is higher than in the general population using the NIH criteria. Methods. We included all consecutive women with IIH of child-bearing age seen at a hospital-based neuro-ophthalmology clinic between the years 2000–2005. All consenting women included in this study filled-out a screening questionnaire aimed at identifying women at risk for PCOS. The endocrinologist examined each patient suspect of PCOS as well as their biochemical results and diagnosed PCOS according to NIH criteria. The prevalence of PCOS in these women with IIH was compared with the reported prevalence of PCOS in the general population. Results. Out of 58 women with IIH who completed the study, definite PCOS was diagnosed in nine women (9/58; 15.5%). We found a significantly higher prevalence of PCOS using the NIH criteria among the IHH study group (15.5%, P=0.001) compared to the general population (8.7%). Conclusions. The prevalence of PCOS is higher among patients with IHH, compared to the general population. We suggest a novel screening questionnaire to aid in the identification of women with IIH at risk for PCOS.